Особливості сучасного шрифтового плакату - Доценко, Д. (My University, 2020)
A poster is a printing publication in the form of one or more sheets of printed material of any format. By the nature of the artistic material posted, posters can be graphic, containing a drawing, photograph, installation or any special image without text or with a small explanatory text; font containing only text
Keywords: шрифтовий плакат